Does public spending reflect the need for health: A cross-sectional analysis at district level in India - Shankar Prinja; Atul Sharma; Aarti Goyal; V R Muraleedharan (Wolters Kluwer Medknow Publications, 2024)
Background: There is mixed evidence on the extent of association between the allocation of public revenue for healthcare and its indicators of need. Objective: In this study, we examined the relationship between allocations through state health financing (SHF) and the Central Government with infant mortality. Materials and Methods: District-wise infant mortality rate (IMR) was computed using National Family Health Survey-4 data. State-wise data for health budgets through SHF and National Health Mission (NHM, a Centrally Sponsored Scheme), were obtained for the year 2015-16. We used a multivariable analysis through generalized linear model method using identity-link function. Results: We found per capita SHF (₹3169) to be more than 12 times that of public health spending per capita through NHM (₹261). IMR was lower in districts with higher SHF allocation, although statistically insignificant. The allocation through NHM was higher in districts with higher IMR, which is statistically significant. Every unit percentage increase in per capita net state domestic product and female literacy led to 0.31% and 0.54% decline, while a 1% increase in under-five diarrhoea prevalence led to 0.17% increase in IMR. Conclusion: The NHM has contributed to enhancing vertical equity in health-care financing. The States' need to be more responsive to the differences in districts while allocating health-care resources. There needs to be a focus on spending on social determinants, which should be the cornerstone for any universal health coverage strategy.